Performance Comparison between Direct Method and Tree-code used in N-body Simulation using Python - Muhammad Isnaenda Ikhsan (Journal of Multidisciplinary Academic, 2020)
N-body simulation is a great tool to study the dynamics of many body system in astronomy. There a many method that could be used to perform N-body simulation. In this study, we compare two methods, direct method and tree-code to perform N-body simulation code written in Python. The advantages of direct method are it’s very straightforward and could be very accurate if we want to, the disadvantages are this method could take a lot of computational resources. In other hand, tree-code could perform much better in term of computational time, but lack of accuracy and limited to certain cases application. After performing N-body simulation using both method we found that simulation using both methods is very possible to be done in a computer with modest specification. The direct method and tree code perform similarly in small N (N100). In term of energy conservation, both methods perform well and similar.